Helical structure in cyclic peptides: effect of N-methyl amides versus esters. Issue 89 (24th October 2022) - Wu, Chongyang; Hoang, Huy N.; Hill, Timothy A.; Lim, Junxian; Kok, W. Mei; Akondi, Kalyani; Liu, Ligong; Fairlie, David P.
Abstract : Cyclic peptides with esters but not N -methyl amides are the smallest known alpha helices in water and can enter cells. Abstract : An alpha helical turn can be reproduced in a cyclic pentapeptide if the first and fifth amino acid sidechains are correctly joined. Here structural studies (CD, NMR, in silico ) reveal why N -methylation at positions not involved in hydrogen bonds disrupts helicity whereas ester bonds can maintain helicity and promote greater cell uptake.